The place of fashion in A Illustration and Le Monde Illustre: dialogues and appropriations - Luca, Tania Regina de [UNESP] (Assoc Brasileira Estudos & Pesquisas Moda, 2020)
In this article, attention focuses on the fashion content disseminated by A Illustracao (Paris, 1884-1892), a periodical that circulated in Portugal and Brazil, but which maintained close relations with the French Le Monde Illustre (Paris, 1857-1940). The objective is to verify the exchanges between these publications regarding the section dedicated to fashion. The analysis of this material poses thought-provoking questions about the circulation of images, the notion of authorship and the sharing of a common imaginary about the notions of fashion and elegance. It is worth highlighting that the so called illustrations made up a specific sector of the periodicals, whose origin dates back to the mid-nineteenth century.
Keywords: Illustrated magazines; Fashion; Graphic design; Circulation of texts and images